Peran Gereja Dalam Memepersiapkan Umat Katolik Menuju Pemilihan Umum (Pemilu) 2024 - Martalia Odi; Intansakti Pius X (Jurnal Magistra, 2023)
The church essentially does not only refer to a physical structure or an organization but also as a community of Catholic believers. The Church is part of the world so the Church also takes part in the development and progress of the world, including participating in political life. This research aims to understand the extent of the church's role in preparing Catholics for the 2024 General Election, to find out the causes of Catholics' reluctance to participate in politics and the church's efforts to prepare Catholics for the 2023 Election. This research uses library methods by collecting information, analyzing and develop understanding of the information obtained. From the information obtained, it can be seen that the Church's ministry in the field of politics is a calling for the church to carry out its mission in the world as an embodiment of the Kingdom of God which is rooted in the Catholic faith.